Report of the Task force on Social and Economic Aspects of Conservation for the Environment and Forests Sector for the Eleventh Five Year Plan (2007-2012) - Planning Commission (Planning Commission Government of India, 2003)
The Task Force Report on Social and Economic Aspects of Conservation for the Environment and Forests Sector, established under India’s Eleventh Five Year Plan (2007-2012), examines the integration of biodiversity conservation with socio-economic development. Anchored in the Biological Diversity Act (2002) and the Convention on Biological Diversity, the report emphasizes recognizing traditional knowledge and practices of local and indigenous communities, who rely on biological resources for their livelihoods. Key findings highlight governance challenges in Biodiversity Management Committees, marginalization of community roles, and the need for inclusive conservation strategies. Recommendations include empowering gram sabhas, implementing equitable benefit-sharing mechanisms, enhancing legislative frameworks, strengthening institutional collaboration, and building community capacity. The report concludes that effective conservation must synergize ecological objectives with human development, ensuring local communities are active participants and beneficiaries in biodiversity management.
Government of India Planning Commission New Delhi
Keywords: Biodiversity Conservation; Socio-Economic Development; Local Communities; Traditional Knowledge; Benefit-Sharing; Biodiversity Management Committees; Governance; Environmental Policy; Genetic Resources; Capacity Building; Institutional Frameworks; Eleventh Five Year Plan